Paul, the Jewish theologian : a Pharisee among Christians, Jews, and Gentiles - Young, Brad, 1955- (Hendrickson Publishers, 1997)
"Paul the Jewish Theologian reveals Saul of Tarsus as a man who, though rejected in the synagogue, never truly left Judaism. Author Young disagrees with long held notions that Hellenism was the context which most influenced Paul's communication of the Gospel. This skewed notion has led to widely divergent interpretations of Paul's writings. Only in rightly aligning Paul as rooted in his Jewishness and training as a Pharisee can he be correctly interpreted. Young asserts that Paul's view of the Torah was always positive, and he separates Jesus' mission among the Jews from Paul's call to the Gentiles."